2007
DOI: 10.1111/j.1939-1676.2007.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function in Cats with Hyperthyroidism Before and After131I Therapy

Abstract: Background:The clinical significance of high serum concentration or activity of markers of liver damage in cats with hyperthyroidism is unknown.Objective: To evaluate serum markers of liver function and damage, and ultrasonographic changes in cats with hyperthyroidism and with high liver enzymes, and to determine if abnormalities resolve after treatment with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…In total, 123/217 (56.7%) had an elevation in ALT, 53/215 (24.7%) had an elevation in ALP, and 29/186 (15.6%) had an elevation in AST. This finding is lower compared to 75.0–78.9% shown in previous reports with fewer hyperthyroid cats ( 9 , 15 ). Our study is the first to report the magnitude of ELEZ in a large cohort of cats presenting for I-131 treatment, with ~8% of cats having ALT >500 IU/L.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…In total, 123/217 (56.7%) had an elevation in ALT, 53/215 (24.7%) had an elevation in ALP, and 29/186 (15.6%) had an elevation in AST. This finding is lower compared to 75.0–78.9% shown in previous reports with fewer hyperthyroid cats ( 9 , 15 ). Our study is the first to report the magnitude of ELEZ in a large cohort of cats presenting for I-131 treatment, with ~8% of cats having ALT >500 IU/L.…”
Section: Discussioncontrasting
confidence: 68%
“…A previous small prospective observational study showed that hyperthyroid cats can have normal liver function and no sonographic abnormalities within their livers despite ELEZ, and all the hyperthyroid cats in that study had NLEZ following I-131 therapy ( 15 ). In the present study with a larger cohort of cats, total thyroxine concentration had a positive correlation with liver enzyme activity elevations, and all cats with STFU or LTFU had NLEZ following euthyroidism after successful I-131 treatment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“… 25 27 Although previous recommendations included evaluating hyperthyroid cats with ALP or ALT activity >500 IU/L for concurrent disease, 2 , 14 , 15 further experience has revealed that the changes seen in the liver secondary to hyperthyroidism usually do not affect liver function testing, such as paired serum bile acids, so such testing may not be warranted. 28 In addition, histologic evaluation of the liver in cats with hyperthyroidism reveals nonspecific and mild changes, 4 and liver enzyme changes associated with hyperthyroidism usually return to within the reference interval with successful management of the disease. 29…”
Section: Clinical Presentationmentioning
confidence: 99%